Identification of peptides derived from ripened Mihalic cheese and promising properties: in silico and in vitro approaches - Altuntas, Seda; Altuntas, Volkan (Springer, 2025)
Dairy products, particularly fermented ones like cheese, are abundant sources of bioactive peptides (BPs) that hold poten-tial health benefits. This study focuses on investigating the peptide profiles of Mihalic cheese, a traditional Turkish hard-brined cheese, employing both in vitro and in silico approaches. This study compares these two methodologies and assesses the potential of in silico digestion for predicting the bioactive peptide profile of dairy products. The in vitro analysis revealed a significant increase in the number of peptides with lengths of <= 10 amino acids after hydrolysis. While 7.7% of the water-soluble peptide extract (WSPE) fraction contained bioactive peptide sequences comprising more than 20 amino acids, all bioactive peptides detected in the hydrolysate of Mihalic cheese consisted of 7-20 amino acids in length. Furthermore, the in vitro analysis identified 30 peptides with various biological activities such as antioxidant, antimicro-bial, angiotensin-converting enzyme (ACE) inhibitory, DPP-IV inhibitory etc., with beta-CN contributing the most to these bioactive peptides. Despite the potential of in silico methods, there was limited overlap with in vitro findings. While in silico analysis predicted a broader range of bioactive peptides, including 17 ACE-inhibitory peptides, only ten peptides and also only three bioactive peptides were identified by both approaches. While in silico tools are valuable for prediction, they may not fully replicate the complex dynamics of actual enzymatic digestion. This highlights the need to improve results by using more combined in vitro and in silico approaches in studies on the prediction of bioactive peptides in food products.
Keywords: In silico analysis; In vitro analysis; Digestion; Dairy peptides; Bioactive peptides